2022
DOI: 10.1088/1361-6463/aca105
|View full text |Cite
|
Sign up to set email alerts
|

Ion dynamics in the magnetic nozzle of a waveguide ECR thruster via laser-induced fluorescence spectroscopy

Abstract: Xenon ion velocity is mapped in the magnetic nozzle of a circular waveguide electron cyclotron resonance thruster operating at 5.8 GHz by means of laser-induced fluorescence spectroscopy in the near-infrared spectral range. An array of thruster operational parameters are explored to investigate the influence on the acceleration profile and terminal ion velocity. Owing to several mechanisms which broaden the measured spectra, e.g. Paschen-Back/Zeeman effect, inference of the most probable velocity along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Results in agreement with these were obtained through LIF measurements performed on this thruster in Ref. 23, where the spread in ion energies was referred to as axial kinetic temperature. In the present study, ion temperatures in the order of 4000-10 000 K were found for most of the cases.…”
Section: B Electrostatic Probe Measurementssupporting
confidence: 70%
See 2 more Smart Citations
“…Results in agreement with these were obtained through LIF measurements performed on this thruster in Ref. 23, where the spread in ion energies was referred to as axial kinetic temperature. In the present study, ion temperatures in the order of 4000-10 000 K were found for most of the cases.…”
Section: B Electrostatic Probe Measurementssupporting
confidence: 70%
“…Indeed, the LIF measurements in Ref. 23, revealed a mean ion velocity of À500 m/s directed toward the backplate at z ¼ À10 mm (middle of the discharge chamber) for the same thruster design as in this study.…”
Section: Assessment Of Partial Efficienciessupporting
confidence: 62%
See 1 more Smart Citation